Effectiveness Differences of Green Betel Leaves (Piper Betle Linn) and Red Betel Leaves (Piper Crocatum Ruis & Pav) Extract in Second Degree Burns Treatment in Increasing Granulation Tissue Thickness on Male White Rats (Rattus norvegicus) Strain Wistar - Mohammad Fendi Nuryahya (LPPMK STIKES Widyagama Husada, 2020)
Burn usually happened at home and the most common are second degree burns. Betel leaves is a natural subtances that have active ingredients such as saponin, tannin, flavonoid, and atsiri essential oil. Betel leaves is used to accelerate wound healing process. This study aims to find out effectiveness differences of green betel leaves (piper betle linn) and red betel leaves exstract (piper crocatum Ruiz & Pav) on granulation tissue thickness in second degree burns treatmen on male white rats (Rattus norvegicus) strain wistar. This study method used is true experiment post-test only control design. The samples were 18 male white rats (Rattus norvegicus) strain wistar. Sampling method used simple random sampling which devided in two intervention group measuring granulation tissue thickness on 14th day under microscop OLYMPUS XC10 (40x). Data were analyzed using independent t-test. The results is statistically significant difference in granulation tissue thickness between two treatment groups (p=0,000). The mean for granulation tissue thickness in green betel leaves extract intervention group was 210,01 µm (131,03 µm – 267,25 µm) and 323,12 µm (267,58 µm – 381,70 µm) in red betel leaves extract. It can be concluded that there are a defference between green betel leaves (piper betle linn) and red betel leaves (piper crocatum Ruiz & Pav) extract efectiveness in increasing of granulation tissue thickness in second degree burns. From this research there are opportunities in the use of red betel leaves extract on burns treatment, but advanced research should be done before applied to humans. Keywords : Green betel leaves; red betel leaves; granulation tissue thickness; second degree burns.